2011
DOI: 10.1002/fam.1108
|View full text |Cite
|
Sign up to set email alerts
|

Cracking behavior of glazings with different thicknesses by radiant exposure

Abstract: Fourteen experiments on cracking behavior of glazings with thicknesses of 3, 6, 8, and 10 mm by radiant exposure were carried out with a new experimental apparatus. The radiant power was controlled proportional to time square to simulate a time‐squared growth fire. An infrared thermal imaging camera was employed to monitor the temperature field of the unexposed glazing surface. Other important parameters including incident heat flux, local gas temperature, exposed surface temperature, and time of the first cra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 26 publications
3
19
0
Order By: Relevance
“…Results from the experiments showed that no fallout occurred below an average heat flux of 20 kW/m 2 . This is in line with the findings by Li et al [19] whose research has shown that a radiant heat flux of only 4-5 kW/m 2 caused glass cracking but did not cause glass fallout. The glass cracking heat flux limit of 4-5 kW/m 2 has also been proposed by Mowrer [20] and it has been widely accepted as a glass fallout criterion.…”
Section: Resultssupporting
confidence: 81%
“…Results from the experiments showed that no fallout occurred below an average heat flux of 20 kW/m 2 . This is in line with the findings by Li et al [19] whose research has shown that a radiant heat flux of only 4-5 kW/m 2 caused glass cracking but did not cause glass fallout. The glass cracking heat flux limit of 4-5 kW/m 2 has also been proposed by Mowrer [20] and it has been widely accepted as a glass fallout criterion.…”
Section: Resultssupporting
confidence: 81%
“…Comparision between the tested and MC-Glaz predicted temperatures of the exposed glazing surface for Test 12, 10 mm galzing, relative errors are also provided. Reproduced with kind permission from Wiley [23]. Because of data limits, only pan fire sizes of 0.6 m  0.6 m and 0.9 m  0.9 m were considered [7].…”
Section: Comparison With Experimental Data: Varying Glazing Thicknessmentioning
confidence: 99%
“…The experimental conditions of Test 1 for 3 mm glazing and Test 7 for 8 mm glazing from [23] are used to examine these influencing factors. Figure 14 shows that the time of first cracking increases with an increase of s/H ratio, while it decreases with an increase of Young's modulus.…”
Section: Factors Influencing Cracking Criterionmentioning
confidence: 99%
See 2 more Smart Citations